Plan of work of a social teacher in a school for suicide prevention - Хамитова, Ісламия; Атемкулова, Назира (Pedagogy and Psychology, 2021)
According to the suicidal state in the world, Kazakhstan ranks third after China and Russia. This situation among children and young people gives reason to think about the education of children in preschool age, especially in primary school. Starting from the youngest years, it is necessary to instill in their consciousness and sense of valuing their own life and the lives of others. In order to focus the attention of social educators on this problem, we offer a plan of work with students and their parents. An important way to overcome suicide and deviant behavior among adolescent children is, firstly, to provide preschool organizations with social teachers; secondly, to work with primary school students, to strengthen a separate social teacher; thirdly, to include an event on the prevention of suicide and deviant behavior among students in the work plan of a social teacher of small schools.